Reactive surface organometallic complexes observed using dynamic nuclear polarization surface enhanced NMR spectroscopy. Issue 1 (26th August 2016) - Pump, Eva; Viger-Gravel, Jasmine; Abou-Hamad, Edy; Samantaray, Manoja K.; Hamzaoui, Bilel; Gurinov, Andrei; Anjum, Dalaver H.; Gajan, David; Lesage, Anne; Bendjeriou-Sedjerari, Anissa; Emsley, Lyndon; Basset, Jean-Marie
Abstract : Reactive surface species immobilized inside porous materials with suitably small windows can be studied by DNP SENS. Abstract : Dynamic Nuclear Polarization Surface Enhanced NMR Spectroscopy (DNP SENS) is an emerging technique that allows access to high-sensitivity NMR spectra from surfaces. However, DNP SENS usually requires the use of radicals as an exogenous source of polarization, which has so far limited applications for organometallic surface species to those that do not react with the radicals. Here we show that reactive surface species can be studied if they are immobilized inside porous materials with suitably small windows, and if bulky nitroxide bi-radicals (here TEKPol) are used as the polarization source and which cannot enter the pores. The method is demonstrated by obtaining significant DNP enhancements from highly reactive complelxes [(Si–O–)W(Me)5 ] supported on MCM-41, and effects of pore size (6.0, 3.0 and 2.5 nm) on the performance are discussed.